The Concept of Regulating Forest Management in a Region Subject to High Environmental Pressure - Borecki, Tomasz; Łopiński, Łukasz; Kędziora, Wojciech; Orzechowski, Michał; Wójcik, Roman; Stępień, Edward (Forests, 2018)
In modern forestry, the complexity of the planning process is increasing, specifically in the context of the sustainable use of forest resources and its adaptation to climate changes. This article presents the concept of forest use regulation promoting the sustainable forestry development in forest management planning. A method for defining a synthetic criterion of assessing important features of stand structure was proposed, which would enable the classification of stands in terms of needs and the urgency of their transformation (reconstruction) or suitability for longer standing. As a result, such a concept may ensure the preservation of the relative uniformity of logging use and the improvement of age structure as well as an increase of natural values of the forest, regardless of a stand’s age. The concept was tested on a large forest complex (over 0.5 million hectares) subjected to intense environmental pressure (Silesian Region in Poland). We prepared long-term individualistic development forecasts, separately for area and volume. Based on this, we followed the cutting uniformity principle in the analysed time period by calculating a long-term average of cutting allowance. It was determined by averaging the projected usage size in moving window and eventually was adopted as the cutting upper limit in the whole analysed period. The proposed size of cuts in each period resulted from the relation between the average value and the forecast. Three sets of stands of the differentiated urgency of interventions were distinguished: I—well-stocked and stable stands (no need of intervention)—55% of stands area, II – acceptable stands (not urgent intervention needed)—35% and III—poor stands (urgent intervention needed)—10%. This concept joins top-down and bottom-up approach of cutting uniformity that focuses stand’s status instead of its age or dimensions.